The need for research in African music - Hyslop, Graham H. (International Library of African Music, 1964)
Two years ago, through the generosity of the Rockefeller Foundation, I was given the opportunity of touring East, Central, South and West Africa, and the Congo, to discover who is doing what in the practice and study of traditional African music. I was joined in West Africa by Henry Owuor, who has himself done a considerable amount of work on the folk music of the Luo people. The original idea behind the tour was the conviction that whereas there are many people who are involved one way or another in the practice and study of African music, there has so far been very little contact between the parties concerned. It was felt, therefore, that a review of musical activity throughout Africa was long overdue, so that some kind of overall picture might be obtained, however incomplete.
Keywords: Ethnomusicology; Music; Musicology; Africa; Education; African Music; Republic of the Congo (Léopoldville)